An Analysis of Students’ Difficulties in Reading Comprehension at Eleventh Grade of Senior High School 8 Jambi City - Aini Aini; Nurul Fitri; Siti Aisyah (JELT: Journal of English Language Teaching, 2023)
The aim of this research is to identify the difficulties in reading comprehension faced by the eleventh-grade students at SMAN 8 Jambi City. This was qualitative research with a phenomenological approach. The subject of the research was the eleventh-grade students at Senior High School 8 Jambi City in Academic Year 2022/2023. The technique of collecting the data was a Reading test. The research used the technique of analyzing the data reduction, data display, and conclusion drawing/verification. The result of the research shows that there are 34,1% of students have difficulties understanding to find the main idea of the text with a total of incorrect is 68. Moreover, there are 21,1% of students have difficulties knowing the meaning of several vocabulary words in the text with a total of incorrect is 42. There are 18,6% of students who have difficulties understanding and making inferences from the text with a total of incorrect is 37. Lastly, there are 26,1% of students have difficulties in understanding to look inferring the meanings of particular words from the text.